Controlled modulation of serum protein binding and biodistribution of asymmetric cyanine dyes by variation of the number of sulfonate groups - Hamann, Franziska M.; Brehm, Robert; Pauli, Jutta; Grabolle, Markus; Frank, Wilhelm; Kaiser, Werner A.; Fischer, Dagmar; Resch-Genger, Ute; Hilger, Ingrid (Molecular Imaging, 2011)
To assess the suitability of asymmetric cyanine dyes for in vivo fluoro-optical molecular imaging, a comprehensive study on the influence of the number of negatively charged sulfonate groups governing the hydrophilicity of the DY-67x family of asymmetric cyanines was performed. Special attention was devoted to the plasma protein binding capacity and related pharmacokinetic properties. Four members of the DY-67x cyanine family composed of the same main chromophore, but substituted with a sequentially increasing number of sulfonate groups (n 5 1-4; DY-675, DY-676, DY-677, DY-678, respectively), were incubated with plasma proteins dissolved in phosphate-buffered saline. Protein binding was assessed by absorption spectroscopy, gel electrophoresis, ultrafiltration, and dialysis. Distribution of dye in organs was studied by intraveneous injection of 62 nmol dye/kg body weight into mice (n 5 12; up to 180 minutes postinjection) using whole-body near-infrared fluorescence imaging. Spectroscopic studies, gel electrophoresis, and dialysis demonstrated reduced protein binding with increasing number of sulfonate groups. The bovine serum albumin binding constant of the most hydrophobic dye, DY-675, is 18 times higher than that of the most hydrophilic fluorophore, DY-678. In vivo biodistribution analysis underlined a considerable influence of dye hydrophilicity on biodistribution and excretion pathways, with the more hydrophobic dyes, DY-675 and DY-676, accumulating in the liver, followed by strong fluorescence signals in bile and gut owing to accumulation in feces and comparatively hydrophilic DY-678-COOH accumulating in the bladder. Our results demonstrate the possibility of selectively controlling dye-protein interactions and, thus, biodistribution and excretion pathways via proper choice of the fluorophore's substitution pattern. This underlines the importance of structure-property relationships for fluorescent labels. Moreover, our data could provide the basis for the rationalization of future contrast agent developments. © 2011 Decker Publishing.
CRIS-Team Scopus Importer:2020-10-13